2010
DOI: 10.3238/arztebl.2010.0254
|View full text |Cite
|
Sign up to set email alerts
|

Modern Lacrimal Duct Surgery From the Ophthalmological Perspective

Abstract: With the methods described here, it is now possible for the first time to perform surgery that obviates the need for a bypass procedure and maintains or restores the normal physiological function of the lacrimal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
1
10
0
9
Order By: Relevance
“…Experimental investigation showed that dacryoendoscopy is a suitable technique for the evaluation and examination as well as treatment of the lacrimal duct system [16]. The improvement of stenting materials, endoscopic devices and a further spectrum of therapeutic options such as laser-technique, microdrill or balloon-dilators brought an enormous advancement [3,4] Some authors report successful use of dacryoendoscopy in children [17][18][19]. But patient numbers have been rather small and doubts as well as controversies still exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental investigation showed that dacryoendoscopy is a suitable technique for the evaluation and examination as well as treatment of the lacrimal duct system [16]. The improvement of stenting materials, endoscopic devices and a further spectrum of therapeutic options such as laser-technique, microdrill or balloon-dilators brought an enormous advancement [3,4] Some authors report successful use of dacryoendoscopy in children [17][18][19]. But patient numbers have been rather small and doubts as well as controversies still exist.…”
Section: Discussionmentioning
confidence: 99%
“…Today, lacrimal stenosis can be eliminated by transcanalicular surgery very often and there is a clear trend towards the usage of this minimally-invasive technique. Even if a therapeutic application is not possible, imaging of the localization and shape of stenosis offers better predictive information for prognosis and choice of a suitable surgery [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, external DCR is a cost effective and equally efficacious procedure with similar success rates and is preferable in cases where endoscopic procedures are contraindicated and in previous failed surgeries. 2 In conclusion external DCR still remains the treatment of choice for NLDO in our setup with very good postoperative results in patients with or without previous history of dacryocystitis.…”
Section: Discussionmentioning
confidence: 99%
“…l " Dakryozystorhinostomie l " Transillumination l " Tränenwegsstenose l " Revision Key words l " endonasal dacryocystorhinostomy l " transillumination l " tear duct obstruction l " revision eingereicht 3. 4 [1] und stellt somit im erschwerten Operationsfeld, wie zum Beispiel bei Revisionsdakryozystorhinostomien, eine wesentliche Hilfestellung für den Operateur dar. Die endonasale DZR wird neben der externen DZR angewandt.…”
Section: Schlüsselwörterunclassified
“…Die endonasale DZR wird neben der externen DZR angewandt. Heutzutage stellen jedoch auch minimalinvasive Verfahren, wie Ballonkatheterdilatation [2], Laserdakryoplastik [3] und Mikrodrill [4], eine Alternative dar. Diese Operationsmethoden zeichnen sich durch geringe Invasivität aus, jedoch sind sie bei komplexeren Tränenwegsstenosen, z.…”
Section: Schlüsselwörterunclassified